Secure Aggregation of Data in Connection-Less Networks (International Journal of Innovative Research in Computer Science & Technology, 2023)
Reliable Minimal Energy Cost Routing  (RMECR) and Reliable Minimum Energy Routing are two  ingenious dynamism- conscious routing algorithms for  wireless ad hoc networks (RMER). Ad hoc network  conditions for dynamism effectiveness, responsibility, and  dragging network continuance are all managed by RMECR.  To develop dynamism-effective and reliable pathways that  outstretch the network's functional continuance, it takes into  account the bumps' dynamism operation, their remaining  battery dynamism, and the tractability of their links. RMER,  on the other phase, is a dynamism-effective routing algorithm  that identifies rows that exercise the least quantum of  dynamism altogether for packet traversal from end to end. For  networks where end- to- end retransmissions or lope- by dance retransmissions guarantee responsibility, RMER and  RMECR are alluded. Simulation simulations demonstrate that  RMECR is able of locating reliable and dynamism-effective  rows analogous to RMER, while contemporaneously  dragging the network's operating life. RMECR is thus a  sophisticated system for dragging the dynamism effectiveness, responsibility, and life of wireless ad hoc  networks. We take into account nanosecond procurators while  intending the RMECR, similar as the dynamism exercised by  the transceiver's processing factors, the ultimate number of  packet retransmissions suffered, packet sizes, and the sequel  of mention packets. This increases the oneness of our work in  comparison to other examinations.
Keywords: Reliable Minimum Energy Cost Routing (RMECR); Reliable Minimum Energy Routing (RMER); Hop- in- Hop (H2H); End to End (E2E)